TREND INDIKATOR PELAYANAN INTENSIVE CARE UNIT DI RSUD Dr. MOEWARDI TAHUN 2014-2018 - Puguh Ika Listyorini; Via Lili Aurista (Jurnal Infokes, 2019)
The Moewardi Regional General Hospital Surakarta has not yet performed the Intensive Care Unit (ICU) service indicator calculation and trend analysis has not been done. The purpose of this study was to determine trends in intensive care unit service indicators in Surakarta Moewardi District General Hospital in 2014-2018. The type of research used is qualitative research, with descriptive research design, and cross sectional approach. The method of collecting data uses documentation studies and interviews. The subjects of this study were five speakers. The object of this study is the data of inpatient patient reports in the ICU. The results showed the average trend value of intensive ICU patients per day increased by 0.5. The trend ratio of patients referred to ICU decreased by 0.006. The trend of ICU mortality rates increased by 0.031. The trend ratio of ICU patients to the number of ICU nurses is 0.064. The trend of the percentage of ICU patients with continued services increased by 0.51. The trend in the percentage of ICU-specific patients decreased by 2.12. The conclusion is that the trend of ICU service indicators tends to increase and decrease. So the advice that researchers can give should improve the quality of service in the form of repairs, adding tools and optimizing the performance of medical personnel so that mortality can be minimized and complete facilities.